INDUSTRIAL STRUCTURE EVOLUTION AND ITS KEY DRIVERS IN UZBEKISTAN’S ECONOMY - Muzaffar Ummatovich Kurbanov; Dmitriy Olegovich Demenchuk (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the evolution of the industrial structure in Uzbekistan’s economy and identifies the key drivers shaping its transformation in the context of economic reforms and structural modernization. The study analyzes changes in sectoral composition, production dynamics, and value-added structure of the industrial sector, with particular attention to the role of technological progress, investment activity, institutional reforms, and state industrial policy. Using official statistical data and analytical methods, the research evaluates how internal and external factors – including foreign direct investment, innovation capacity, resource availability, and market liberalization – have influenced the development and diversification of the industrial sector. The findings reveal that Uzbekistan’s industrial structure has undergone significant transformation, characterized by a gradual shift from resource-based industries toward manufacturing and higher value-added sectors. The article highlights the importance of coordinated industrial policy, technological upgrading, and human capital development in ensuring sustainable industrial growth. The results contribute to a deeper understanding of structural changes in transition economies and provide practical insights for policymakers aimed at enhancing industrial competitiveness and long-term economic development.